2005
DOI: 10.1093/brain/awh453
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal activation of the IL-17/IL-8 axis in opticospinal multiple sclerosis

Abstract: There are two distinct subtypes of multiple sclerosis in Asians, opticospinal (OS-multiple sclerosis) and conventional (C-multiple sclerosis). In OS-multiple sclerosis, selective and severe involvement of the optic nerves and spinal cord is characteristic, though its mechanisms are unknown. The present study aimed to find out possible differences in the cytokine/chemokine profiles in CSF between OS-multiple sclerosis and C-multiple sclerosis and to delineate the relationships between these profiles and neuroim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
220
3
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(245 citation statements)
references
References 71 publications
11
220
3
8
Order By: Relevance
“…Consistently, in the present study, CSF IL-6 was elevated in acute NBD as well as in CP NBD, but not in non-NBD. Previous studies demonstrated that CSF IL-6 was not elevated in patients with multiple sclerosis [22, 23]. Therefore, the determination of CSF IL-6 might be useful for the differential diagnosis of NBD and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in the present study, CSF IL-6 was elevated in acute NBD as well as in CP NBD, but not in non-NBD. Previous studies demonstrated that CSF IL-6 was not elevated in patients with multiple sclerosis [22, 23]. Therefore, the determination of CSF IL-6 might be useful for the differential diagnosis of NBD and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It offers great hope for potential treatment of diseases where IL-17 is recognized as the key inducer of inflammation, as is now Highlights 2871 well documented in arthritis [29], asthma [30], inflammatory bowel disease [31,32] and intra-abdominal abscesses [33]. In multiple sclerosis, little is known about the actual importance of IL-17, although increased numbers of IL-17 mRNA-expressing cells were found to correlate with disease exacerbation [34]. Another question that remains to be solved, is whether anti-IL-17 vaccination can be effective curatively.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17-producing T-helper cells play an important role in the induction of neuroimmune diseases, like MS and its animal model called experimental autoimmune encephalomyelitis (EAE) [Iwakura & Ishigame, 2006.]. This observation is based on the detection of IL-17 levels in both the plaques and cerebrospinal fluid of MS patients [Ishizu et al, 2005].…”
Section: Induction Of Central Nervous System Autoimmunity By Th17 Lymmentioning
confidence: 99%